Source apportionment of PM10 mass and particulate carbon in the Kathmandu Valley, Nepal. (December 2015) - Kim, Bong Mann; Park, Jin-Soo; Kim, Sang-Woo; Kim, Hyunjae; Jeon, Haeun; Cho, Chaeyoon; Kim, Ji-Hyoung; Hong, Seungkyu; Rupakheti, Maheswar; Panday, Arnico K.; Park, Rokjin J.; Hong, Jihyung; et al.
Abstract: The Kathmandu Valley in Nepal is a bowl-shaped urban basin in the Himalayan foothills with a serious problem of fine particulate air pollution that impacts local health and impairs visibility. Particulate carbon concentrations have reached severe levels that threaten the health of 3.5 million local residents. Moreover, snow and ice on the Himalayan mountains are melting as a result of additional warming due to particulate carbon, especially high black carbon concentrations. To date, the sources of the Valley's particulate carbon and the impacts of different sources on particulate carbon concentrations are not well understood. Thus, before an effective control strategy can be developed, these particulate carbon sources must be identified and quantified. Our study has found that the four primary sources of particulate carbon in the Kathmandu Valley during winter are brick kilns, motor vehicles, fugitive soil dust, and biomass/garbage burning. Their source contributions are quantified using a recently developed new multivariate receptor model SMP. In contrast to other highly polluted areas such as China, secondary contribution is almost negligible in Kathmandu Valley. Brick kilns (40%), motor vehicles (37%) and biomass/garbage burning (22%) have been identified as the major sources of elemental carbon (black carbon) in the Kathmandu Valley during winter, while motor vehicles (47%), biomass/garbage burning (32%), and soil dust (13%) have been identified as the most important sources of organic carbon. Our research indicates that controlling emissions from motor vehicles, brick kilns, biomass/garbage burning, and soil dust is essential for the mitigation of the particulate carbon that threatens public health, impairs visibility, and influences climate warming within and downwind from the Kathmandu Valley. In addition, this paper suggests several useful particulate carbon mitigation methods that can be applied to Kathmandu Valley and other areas in South Asia with similar sources and high particulate carbon concentrations. Highlights: High particulate carbon and low secondary inorganic ion levels are characteristic of PM10 data in the Kathmandu Valley. Motor vehicles and biomass/garbage burning sources are the main sources of primary organic carbon. Whereas brick kilns, motor vehicles and biomass/garbage burning sources are the major sources of elemental carbon.